Evaluating Wave Potential and Assessing the Economic Viability of Wave Energy Converters in the South Java Seas - Waskito, Kurniawan Teguh; Yudho, Renaldi H; Yanuar, Yanuar; Rahardjo, Gema P (Department of Naval Architecture - Diponegoro University, 2023)
As an archipelagic nation, Indonesia holds substantial potential for wave energy as a renewable resource. Certain coastlines of islands facing the Indian Ocean, particularly in the western and southern regions, exhibit significant wave energy throughout the year. To identify suitable locations for Wave Energy Converter (WEC) installation, it is essential to assess wave hindcast data. This study utilizes NOAA and ERA5 reanalysis wave data to analyze wave characteristics in Indonesia from 2008 to 2018. Data processing with Ocean Data View is employed to estimate key wave parameters at various locations, including significant wave height, mean wave period, and mean wave direction. Two locations in the South Java seas were identified for WEC installation based on this research. The average values for the period 2008 to 2018 indicate a significant wave height of around 2m, with a maximum height of 5m, a wave period of 10–14s, and a wave direction of 195–210 degrees. Notably, NOAA data suggests a higher estimation of significant wave height compared to ERA5 data. The average annual wave power potential based on ERA5 and NOAA is 164.43 MW/m and 252.15 MW/m, respectively. Furthermore, this study incorporates an economic simulation for the construction of a multi-point absorber WEC. The objective is to offer insights into the Levelized Cost of Electricity (LCOE) and compare it with other WEC technologies. Assuming a WEC capacity of 130 kW, the total construction cost is estimated at 2,093,725, resulting in a Levelized Cost of Energy (LCOE) of 91/MWh.